Development of Knowledge Sharing Model Using Decision Support System In Determine Feasible on the Job Training In Vocational School Using Vikor Method - S Safrizal; A Ambyar; Unung Verawardina (IJISTECH (International Journal of Information System and Technology), 2021)
Decision support system (SPK) as a system that can process input data into one information that can be used as a more accurate decision support for the school in recommending students who meet the categories or requirements in following the Job Training. The system that was built carried out the process of determining decision support based on the Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) method which is able to simplify complex problems in determining feasible to follow the On The Job Trainings based on criteria using formulas whose results are right on target.